Inhibition of TRPC4 channel activity in colonic myocytes by tricyclic antidepressants disrupts colonic motility causing constipation. Issue 19 (12th May 2022) - Jeong, Byeongseok; Sung, Tae Sik; Jeon, Dongju; Park, Kyu Joo; Jun, Jae Yeoul; So, Insuk; Hong, Chansik
Abstract: Tricyclic antidepressants (TCAs) have been used to treat depression and were recently approved for treating irritable bowel syndrome (IBS) patients with severe or refractory IBS symptoms. However, the molecular mechanism of TCA action in the gastrointestinal (GI) tract remains poorly understood. Transient receptor potential channel canonical type 4 (TRPC4), which is a Ca 2+ ‐permeable nonselective cation channel, is a critical regulator of GI excitability. Herein, we investigated whether TCA modulates TRPC4 channel activity and which mechanism in colonic myocytes consequently causes constipation. To prove the clinical benefit in patients with diarrhoea caused by TCA treatment, we performed mechanical tension recording of repetitive motor pattern (RMP) in segment, electric field stimulation (EFS)‐induced and spontaneous contractions in isolated muscle strips. From these recordings, we observed that all TCA compounds significantly inhibited contractions of colonic motility in human. To determine the contribution of TRPC4 to colonic motility, we measured the electrical activity of heterologous or endogenous TRPC4 by TCAs using the patch clamp technique in HEK293 cells and murine colonic myocytes. In TRPC4‐overexpressed HEK cells, we observed TCA‐evoked direct inhibition of TRPC4. Compared with TRPC4‐knockout mice, we identified that muscarinic cationic current (m I cat ) was suppressed through TRPC4 inhibition by TCA in isolated murine colonic myocytes. Collectively, we suggest that TCA action is responsible for the inhibition of TRPC4 channels in colonic myocytes, ultimately causing constipation. These findings provide clinical insights into abnormal intestinal motility and medical interventions aimed at IBS therapy.